Analisis Dampak Pemanfaatan Energi Matahari Terhadap Perubahan Iklim Di Indonesia - Mauladhani, Anisa Eka; ., Sudarti; ., Yushardi (CV. ITTC INDONESIA, 2023)
Examining the possible influence of solar energy on climate change is the purpose of this article. Using the literature study method, the author will then compare various existing publications and theories. The sun is a source of lighting and heating for the earth, where solar activity also influences climate change. Climate change in Indonesia is largely influenced by the use of solar energy. The presence of the sun can influence the occurrence of solar radiation, the amount of solar energy that reaches the earth, the magnetic field that surrounds the planet, and the number of particles emitted by the sun. This also affects the strength of cosmic rays that reach Earth. This affects the dynamics of the atmosphere and oceans as well as the development of clouds and rain. Peak cloud cover occurs when solar activity is at its lowest and cosmic ray output is at its highest. When the sun is active, there are fewer clouds because cosmic rays have lower power. The conclusion drawn is that solar activity has a significant effect on climate change.